The Contribution of the COVID-19 Pandemic Lockdown Restrictions on Vitamin D Levels among Postmenopausal Women in Kerbala Province - Hayder B. Al-Ghreaty; Wasim T. Mahdi Al Masoodi (Indian Journal of Forensic Medicine & Toxicology, 2021)
Objective: To evaluate the prevalence of vitamin D deficiency in postmenopausal women in light of restrictions imposed by the Covid-19 pandemic.Methods: This was a single-center cross-sectional study with total of 167 women patients (post-menopausal :133, pre-menopausal: 24) who were divided into two groups according to age.Result: There were significant negative links between serum T4 hormone levels and each of serum calcium values (r=-0.049, p <0.001) in post-menopausal. Serum T4 hormone levels are negatively correlated to TSH hormone levels (r=-0.032, p < 0.001) but T3 hormone levels shows significantly negative correlation (r=-0.277p<0.001). The correlation between serum T4 hormone levels vs Glucose in patients was significantly negative (r= -0.017, p <0.001),The results show that significant decrease(p<0.01) in serum levels T4, T3 hormone, vit. D in post-menopausal women compared as compared to pre-menopausal, correlation of vitamin D with serum calcium (0.23 and T4, hormone (0.137) was significantly positive, and high fasting glucose in post-menopausal as compared to pre-menopausal . Conclusion: Baseline serum vitamin D levels are inversely related with thyroid hormone in post-menopausal women